2020
DOI: 10.1186/s13054-020-2730-0
|View full text |Cite
|
Sign up to set email alerts
|

New-onset atrial fibrillation and associated outcomes and resource use among critically ill adults—a multicenter retrospective cohort study

Abstract: Background: New-onset atrial fibrillation (NOAF) is commonly encountered in critically ill adults. Evidence evaluating the association between NOAF and patient-important outcomes in this population is conflicting. Furthermore, little is known regarding the association between NOAF and resource use or hospital costs. Methods: Retrospective analysis (2011-2016) of a prospectively collected registry from two Canadian hospitals of consecutive ICU patients aged ≥ 18 years. We excluded patients with a known history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 43 publications
(64 reference statements)
2
38
1
6
Order By: Relevance
“…In a recent analysis of 15,014 patients with critical illness in ICU, 1944 patients had sepsis and 1286 patients had septic shock. NOAF was not associated with increased mortality in critically ill patients in ICU but increased mortality seen among sepsis and septic shock patients with adjusted odds ratio of 1.24 (95% CI 1.1-1.39) and 1.28 (95% CI 1.14-1.44), respectively [ 21 ]. In another large study done in the Netherlands on 1782 patients, 418 patients were found to have 1087 episodes of NOAF and those patients were found to have increased mortality and longer stays in the hospital [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis of 15,014 patients with critical illness in ICU, 1944 patients had sepsis and 1286 patients had septic shock. NOAF was not associated with increased mortality in critically ill patients in ICU but increased mortality seen among sepsis and septic shock patients with adjusted odds ratio of 1.24 (95% CI 1.1-1.39) and 1.28 (95% CI 1.14-1.44), respectively [ 21 ]. In another large study done in the Netherlands on 1782 patients, 418 patients were found to have 1087 episodes of NOAF and those patients were found to have increased mortality and longer stays in the hospital [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study published in Critical Care, Fernando SM and colleagues investigated the impact of new-onset atrial fibrillation (NOAF) on clinical outcomes in critically ill patients [1]. They performed univariate analysis and found that the length of stays (LOS) in ICU and hospital was both longer in the NOAF group versus non-NOAF group.…”
Section: Dear Editormentioning
confidence: 99%
“…The authors would like to thank Drs. Lu and Chen for their comments on our recent article related to outcomes and costs associated with new-onset atrial fibrillation (NOAF) in critically ill adults [1]. Drs.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation (AF) is the most sustained arrhythmia, contributing to short and long-term cardiovascular complications such as hemodynamic instability, stroke, heart failure, and mortality risk (1)(2)(3)(4)(5). Considering the continuous rise in the average life expectancy in recent years and an increase in cardiac morbidity, the occurrence of AF has been increasing sharply in the past two decades.…”
Section: Introductionmentioning
confidence: 99%